A PORTRAIT OF TEACHERS IN TEACHING TOEFL READING - Pranoto, Yohanes Heri; Anselmus Inharjanto; Ega Leovani; Catharina Clara; Florentinus Heru Ismadi (Universitas PGRI Palembang, 2025)
The purpose of this study was to design a TOEFL preparation program for the Rethorica Class of St. Paulus Minor Seminary Palembang, aimed at improving reading skills essential for post-high school education and English proficiency in today's disruptive era. The program, which lasted for 7 days, involved 27 seminarians and integrated lectures, exercises, tests, and discussions. It included pre- and post-tests to measure progress, along with a questionnaire to gather feedback. The reading skills targeted were main idea identification, text organization, direct and indirect question answering. Results showed a significant improvement, as evidenced by a higher score in the post-test compared to the pre-test. Inference statistics revealed a significance value of 0.005, indicating meaningful change. The questionnaire results confirmed that the program effectively supported TOEFL reading skills development. This study offers insights for improving TOEFL preparation programs in seminaries and similar institutions, emphasizing structured training methods to enhance reading skills and test-taking strategies. The originality of this research lies in its focus on seminarians and its empirical evidence of the positive impact of tailored, short-term TOEFL training on their English proficiency.